Chromosomal radiosensitivity in oncological and non-oncological patients with rheumatoid arthritis and connective tissue diseases - Rzepka, Dinah; Schenker, Hannah; Geinitz, Hans; Silberberger, Elisabeth; Kaudewitz, Dorothee; Schuster, Barbara; Kuhlmann, Lukas; Schonath, Miriam; Ayala Gaona, Horacio; Aschacher, Bernhard; Fietkau, Rainer; Schett, Georg; et al. (Radiation oncology, 2023)
The risk of developing late radiotoxicity after radiotherapy in patients with high chromosomal radiosensitivity after radiotherapy could potentially be higher compared to the risk in patients with average radiosensitivity. In case of extremely high radiosensitivity, dose reduction may be appropriate. Some rheumatic diseases (RhD), including connective tissue diseases (CTDs) appear to be associated with higher radiosensitivity. The question arises as to whether patients with rheumatoid arthritis (RA) also generally have a higher radiosensitivity and whether certain parameters could indicate clues to high radiosensitivity in RA patients which would then need to be further assessed before radiotherapy.